FAKTOR-FAKTOR RISIKO LINGKUNGAN RUMAH DAN PERILAKU YANG BERHUBUNGAN DENGAN KEJADIAN INFEKSI SALURAN PERNAFASAN AKUT (ISPA) PADA BALITA DI KELURAHAN KUNINGAN KECAMATAN SEMARANG UTARA - Gita Nurina Ramadhaniyanti; Budiyono Budiyono; Nurjazuli Nurjazulil (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Acute Respiratory Infection (ARI) is a disease caused by bacteria, viruses and fungi. Recapitulation of monthly report of 10 major disease found that ARI in Kuningan village are highest any villages in the work area of Bandarharjo Primary Health Care. The purpose of this study was to analyze the relationship between bedroom population density, the width of house ventilation, bedroom air humidity, smoking habits of family members in the house, the presence of taking children habits in the kitchen while cooking and the habit of burning mosquito coils with ARI incidence in children under five years in the Kuningan Village. This study used an explanatory research with cross sectional design. The population was all children aged 12-59 months in the Kuningan Village with good nutritional status and the status of fully immunized as many as 558 children. Samples were taken using Systematic Random Sampling technique as many as 64 samples. Data analysis using chi square test (CI = 95%, α = 5%). The results indicated that the proportion of poor ventilation with children suffering from ARI 54,3% and 45,7% did not suffer from ARI, smoking habits of family members in the house with children suffering from ARI 56,2% and 43,8% did not suffer from ARI. While the bedroom population density does not qualify as much as 65,6%. It was found that there are relationship between the width of house ventilation (p-value = 0,041) and smoking habits of family members in the house (p-value = 0,014). Variables that did not have significant relationship are bedroom population density (p-value=1,000), bedroom air humidity (p-value=0,586), the presence of taking children habits in the kitchen while cooking (p-value=0,924), and the habit of using mosquito coils (p-value=0,885). Conclutions is the smoking habits of family members in the house is a risk factor of ARI.